INTERNATIONAL PRACTICE ASSISTANCE AT REGIONAL REVENUE DEPARTMENT OF TTU DISTRICT BY STUDENTS OF THE UNIVERSITY OF TIMOR UNIVERSITY DEVELOPMENT AND ECONOMIC MANAGEMENT STUDY PROGRAM - Kolo, Adriana; Mauk, Sarlince Sandy; Mentu, Handrianus (Yayasan Pendidikan Cahaya Budaya Indonesia, 2023)
This community service is carried out by assisting apprenticeship practices at the Regional Revenue Service Office of North Central Timor Regency. With the aim of providing opportunities for students to apply theory and knowledge during lectures to practical realities in the world of work. The method used is the Field Work Practice at the TTU Regional Revenue Service Office. Assistance is carried out by 4 students with an effective period of 50 working days. As for the results of this internship work practice, apprentices can learn directly about the use of local tax applications, attend PAD evaluation meetings, assist the head of the billboard-themed data collection section, file taxes, filing incoming and outgoing letters, operate a local tax receipt printing machine, recapitulate mineral tax determination. and non-metal as well as assistance from TTU Regency.